2009
DOI: 10.1177/0269215508095360
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence and mental health rehabilitation

Abstract: Rehabilitation services should ensure that they have rehabilitation goals that strengthen individuals' sense of coherence. Further investigation is required into the development of rehabilitation programmes with sense of coherence theory as part of their foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 19 publications
(29 reference statements)
1
37
0
1
Order By: Relevance
“…Consistent with the experience of talk therapy just described, Griffiths (2009) concluded in a literature review that it might be advantageous to include therapy goals based on the sense of coherence in mental health rehabilitation with people having various mental health challenges such as schizophrenia, psychosis, addiction, and depression. Menzies (2000) elaborated on how a psychiatric nurse might apply a salutogenic approach to a person diagnosed with schizophrenia: talking about managing and coping with symptoms and problems, fostering hope by discussing possibilities, and supporting increased consciousness of abilities and skills, thus contributing to self-esteem, identity, and sense of coherence.…”
Section: Other Perspectives On Salutogenesis and Therapymentioning
confidence: 74%
“…Consistent with the experience of talk therapy just described, Griffiths (2009) concluded in a literature review that it might be advantageous to include therapy goals based on the sense of coherence in mental health rehabilitation with people having various mental health challenges such as schizophrenia, psychosis, addiction, and depression. Menzies (2000) elaborated on how a psychiatric nurse might apply a salutogenic approach to a person diagnosed with schizophrenia: talking about managing and coping with symptoms and problems, fostering hope by discussing possibilities, and supporting increased consciousness of abilities and skills, thus contributing to self-esteem, identity, and sense of coherence.…”
Section: Other Perspectives On Salutogenesis and Therapymentioning
confidence: 74%
“…Several studies underline that rehabilitation services should ensure that they have rehabilitation goals that strengthen individuals' sense of coherence (Engström & Janson, 2009;Griffiths, 2009;Kaiser, Mattsson, Marklund, & Wimo, 2001;Kaiser et al, 2006;Lillefjell, 2008;Newton, 1999). Engström and Janson (2009) found that a high level of sense of coherence counteracts short as well as long-term sickness absence.…”
Section: Descriptive Researchmentioning
confidence: 99%
“…Salutogenic theory is found to help explain the process of recovery for those with mental health issues (Griffiths, 2009); there is substantial evidence that sense of coherence plays a central role in coping with stressors in the rehabilitation process, and that it contributes to mental health and psychosocial functioning. Moreover, sense of coherence is found to increase through work rehabilitation programs and re-employment (Lillefjell & Jakobsen, 2007;Vastamaki, Moser, & Paul, 2009).…”
Section: Intervention Researchmentioning
confidence: 99%
See 2 more Smart Citations